Do Permanent and Temporary Cash Flows Affect Corporate Buybacks? - V. Bhama (Финансы: теория и практика)
Equity buyback decisions are critical commitments, depending on the cash position of a firm.   The purpose of this study was to examine the effects of cash flow volatility on the buyback decisions of Indian corporate firms.   The sample comprised 132 Indian companies listed on the Bombay Stock Exchange from 2012–2019. The selected firms had non-significant abnormal returns (after buyback announcements) that aroused the inquisitiveness to explore the real motivation behind repurchases across firms with permanent and volatile cash flows. The results of ordinary least squares regression suggested that large cash holdings were unrelated to the buybacks with coefficient values –0.02 and 0.01 for firms with permanent and volatile operating cash flows, respectively. Firms with considerable cash flows exhibited a low tendency to buy back their shares. The repurchases served mostly as signaling tools meant to enhance the value of stocks that were potentially undervalued. Thus, the undervaluation of stocks (with a beta of –0.38) seemed to have significantly affected the repurchase decision in association with the constant or volatile cash flows of the firms. Further, small firms appeared to engage more frequently in buybacks given their lower market-to-book ratios.